Criminal expertise and offender decision-making. An experimental analysis of how offenders and non-offenders differentially perceive social stimuli - Topalli, Volkan (The British journal of criminology, 2005)
The article presents an experimental analysis of how offenders and non-offenders differentially perceive social stimuli. If differential cognitive functioning patterns are assumed to exist between offenders and non-offenders, then more specific questions regarding the nature of those differences must be addressed. Cognitive operations specifically germane to the planning or execution of crimes are of particular interest to criminologists as they relate to offender decision-making. Various work has focused on how burglars assess the immediate physical environment and settings within which their crimes occur